Integration of Maslow's Hierarchy of Needs Theory and Maqāṣid al-Sharīʿah for Optimizing Childcare in Long-Distance Situations - Nisa', Ihda Shofiyatun; Firdausi, Mir'atul; Sugitanata, Arif (IAIN Ponorogo, 2025)
Modern life often requires family members to live apart due to work or educational obligations, presenting challenges for effective parenting. This study examines strategies to optimize child-rearing in the context of physical separation by integrating Maslow’s hierarchy of needs with the principles of Maqāṣid Syarīʿah. Using a qualitative, descriptive-analytical approach, the study draws on a range of scholarly sources, including journals and books. The findings demonstrate that children’s essential needs—physiological, safety, love, esteem, and self-actualization—can still be met through consistent, technology-mediated communication, such as video calls and messaging. The involvement of extended family or caregivers also plays a critical role in supporting children’s daily needs. Maslow’s framework emphasizes structured emotional support, while Maqāṣid Syarīʿah highlights the preservation of religion, life, intellect, lineage, and property. Together, these frameworks offer a comprehensive model for distant parenting. The study concludes that effective parenting across distances is achievable through intentional collaboration, the appropriate use of digital tools, and alignment with both psychological and spiritual development goals.